THE STRUCTURES OF WRP “LIMITED EDITION” ADVERTISEMENT - MISKIYAH, URFI ZAKIYATUL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Discourse Analysis, Structured Content, Macrostructure, Microstructure, WRP Limited EditionDiscourse analysis is the subject that deals with the analysis of production and interpretation of the text. It concernswith the forms of language used. This research has one problem of the study that is how the WRP Limited Edition advertisement is constructed. This research is conducted to analyze the structure of WRP limited Edition advertisement.This research used a qualitative approach to analyze the data. The data are taken from the transcription of the utterancesin the advertisement.The source of the data is the script of the model’s utterance and the description of what she is doing in the advertisement. The data are taken from www.youtube.com on February 27, 2014.The results reveal that there are three macrostructures based on the macrorule analysis of the advertisement. The first is the deletion rule in Wanita yang limited edition bisa memakai semua jenis baju karena WRP “The limited edition woman fit in every shirt because of WRP”. The second is the generalization rule which is Wanita yang gemuk menjadi langsing setelah mengonsumsi WRP “The fat women becomes slim after consuming WRP”. The last is the construction rule,in Dia frustasi dengan kegemukannya sebelum dia mengonsumsi WRP “She frustrates with her fat before she consumes WRP”. Moreover, in microstructure analysis, the advertisement maker uses adverbial time that show something happen in the past and in the present. The third structure reveals that the superstructureofthe product is guaranteed to solve the problem of the body shape which can be proven by the illustration of the advertisement.Based on the result of the analysis, it can be concluded that there are structures that are used by the advertisement maker to reveal the content of advertisement. It can be seen from the lexical choice that the advertisement maker uses the plot of the advertisement. The researcher suggeststhat the next researchers apply a structured content in discourse analysis so that it will be helpful for the readers to develop their knowledge about the structured content.